Schreibersite: an effective catalyst in the formose reaction network. (9th May 2018) - Pallmann, S; Šteflová (neé Svobodová), J; Haas, M; Lamour, S; Henß, A; Trapp, O
Abstract: We report on the ability of the meteoritic material schreibersite to catalyze the generation of higher sugars from simple carbohydrates in the formose reaction network. Since the analysis of carbonaceous meteorites like the Murchison meteorite it has become generally accepted that a substantial amount of organic material has been delivered to the early earth and, therefore, ought to be considered in scenarios for the origin(s) of life. Also for the open question of accessible phosphorus sources, an extraterrestrial material called schreibersite has been identified that is capable of releasing soluble and reactive phosphorus oxyanions that would react with organics to form for instance nucleotides and membrane associated molecules. We have reinvestigated this material using capillary electrophoresis to monitor its corrosion process in water and probed its ability to phosphorylate a wide range of organics. Although showing a poor reactivity of schreibersite, we have found that the material catalyzes the aldol reaction of small carbohydrates forming larger sugar molecules. This reaction in the formose reaction network is a prebiotically likely route to biologically relevant sugars. The results of our study present one of the first instances of connecting extraterrestrial material to prebiotic chemistry on the early earth.